Resource usage of LTE networks for machine-to-Machine group communications: Modeling and analysis. (October 2018) - Chu, Eunmi; Yoo, Hoyoung; Jung, Bang Chul
Abstract: Machine nodes (MNs) such as monitoring devices and utility devices can be handled with machine-to-machine (M2M) group communications in commercial 3GPP LTE networks. However, the current LTE networks are designed for human-oriented communication, i.e., human-to-human (H2H) communication, as a main service. Hence, the M2M group communications may utilize a limited amount of radio resource in the LTE networks so that they do not degrade the quality-of-services (QoS) of the H2H communications. Under the resource limitation, the MNs in the M2M communication group may suffer resource contentions when they simultaneously send uplink data packets to a base station (BS). In this paper, we first mathematically model the overall procedure of the M2M group communications. Then, we also optimize the system parameters for the M2M group communications to maximize resource utilization of the LTE networks and minimize the packet transmission delay, while satisfying the resource constraint.